2008
DOI: 10.1126/science.1158298
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Bacterial Infections in Humans with MyD88 Deficiency

Abstract: MyD88 is a key downstream adapter for most Toll-like receptors (TLRs) and interleukin-1 receptors (IL-1Rs). MyD88 deficiency in mice leads to susceptibility to a broad range of pathogens in experimental settings of infection. We describe a distinct situation in a natural setting of human infection. Nine children with autosomal recessive MyD88 deficiency suffered from life-threatening, often recurrent pyogenic bacterial infections, including invasive pneumococcal disease. However, these patients were otherwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
569
3
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 841 publications
(592 citation statements)
references
References 29 publications
15
569
3
5
Order By: Relevance
“…18 By following this strategy, we were able to identify 3 residues that are required for the interaction of MyD88 with IRAKs and for MyD88-dependent activation of NF-B. 18 Remarkably, mutations in one of these residues, glutamic acid 52, was also found in patients affected by recurrent infections, 19 which thus validated our in vitro studies in a physiopathologic setting. Our studies also revealed that the small stretch of residues in the DD of MyD88, constituted by the ␣1, ␣2, ␣3 helices and by the first portion of the ␣4 helix, offers a surface of interaction between MyD88 and IRAKs.…”
Section: Myd88 Inhibition and Human Diseasessupporting
confidence: 61%
“…18 By following this strategy, we were able to identify 3 residues that are required for the interaction of MyD88 with IRAKs and for MyD88-dependent activation of NF-B. 18 Remarkably, mutations in one of these residues, glutamic acid 52, was also found in patients affected by recurrent infections, 19 which thus validated our in vitro studies in a physiopathologic setting. Our studies also revealed that the small stretch of residues in the DD of MyD88, constituted by the ␣1, ␣2, ␣3 helices and by the first portion of the ␣4 helix, offers a surface of interaction between MyD88 and IRAKs.…”
Section: Myd88 Inhibition and Human Diseasessupporting
confidence: 61%
“…By spotlighting NF-κB immunity, these studies paved the way for investigations of children with IPD but without EDA. We found mutations of the genes encoding IL-1R-associated kinase-4 (IRAK-4) and myeloid differentiation primary response gene 88 (MyD88), controlling the canonical Toll-like receptor (TLR) and IL-1R signaling pathways, in children with IPD displaying little clinical and biological inflammation (98,99). These children are otherwise healthy, although they also are vulnerable to invasive staphylococcal disease (100-103).…”
Section: Invasive Pneumococcal Diseasementioning
confidence: 99%
“…Strategies by which both bacterial and viral proteins such as vaccinia virus protein A46R and hepatitis C virus nonstructural protein NS5A target MyD88 signaling to evade immune detection have been described (29). Clinically, rare MyD88 mutations are associated with immunodeficiencies that predispose patients to recurrent life-threatening bacterial infections analogous to MyD88 deficiency in mice that leads to susceptibility to various pathogens (30). Finally, roles for MyD88 signaling in the regulation of inflammation during cancer progression of the intestine (31), liver (32), pancreas (33), and skin (34) are beginning to emerge.…”
Section: Myd88: a Critical Adaptor Protein In Innate Immunity Signal mentioning
confidence: 99%